The Philosophy of Wilfrid Sellars: Queries and Extensions
X, 305 p.
Keywords: In early November 1976 a workshop on the Philosophy of Wilfrid Sellars was held at Virginia Polytechnic Institute and State University in Blacks burg, Virginia. Sponsored by the Department of Philosophy and Religion, the College of Arts and Sciences and the Research Division of the University and organized by Professor Joseph C. Pitt, its aim was to provide a forum in which views of Professor Sellars could be discussed by a group of scholars fully acquainted with this work. Aside from the twelve invited participants, the workshop was attended by interested parties from as far away as Canada. The papers contained in the volume rep resent the results of the discussions held that weekend. With two excep tions the contents are extensively rewritten and revised versions of infor mal talks and presentations. (Rosenberg's paper is here in its original complete version. Rottschaefer was unable to attend. ) This collection is not then the proceedings but the final product derived from work initiated that weekend. The papers reftect both the spirit of the workshop and the work of Professor Sellars in that they represent the fruits of an intense and multi-faceted dialogue. Professor Sellar~' presence and whole hearted participation left us all with more than enough food for thought and a deepened appreciation of both the man and his philosophy. Special thanks are due Thomas Gilmer, Associate Dean of Research for The College of Arts and Sciences and Randal M.